Spectral hole burning effects initiated by uniform signal intensities in a gain-flattened EDFA - Sarmani, A.R.; Sheih, S.J.; Adikan, Faisal Rafiq Mahamd; Mahdi, M.A. (2011)
Spectral hole burning (SHB) effects in a gain-flattened erbium-doped fiber amplifier (EDFA) are demonstrated to be significant in the presence of large signal power around the 1530-1532-nm wavelength range. These are the first effects reported in a setup employing equivalent power level distribution of 40 channels ranging from 1530 to 1561 am. To explain this, the introduction of a new local population variable into the laser equation is required to support the original inversion ratio that is determined by the pump lasers. In the analysis section, spectroscopic parameters and high signal powers are considered to be other contributing parameters to the change in the gain characteristics. An improvement to this theoretical basis is suggested by implementing mathematical modeling to validate similarities between the gain shape of simulation to that obtained in the experiment.